Rooting Medium and Indole-3-Butyric Acid (IBA) Stimulate Adventitious Rooting in Codiaeum ‘Aucubaefolia’ - Dasanayaka, Y.M.H.M.H.; Attanayake , R.M.T.D.; Sawbhagya , L.H.N.; Wickramasinghe , P.A.S.C.; Sandarenu , K.M.S.D.; Gamage , S.N.W.; Hettiarachchi , W.A.B.H.; Dilshan , H.K.L.; Dayarathna , C.R.; Kumarihami, H.M. Prathibhani Chamidha (Universitas Djuanda, 2024)
The bright coloring of Codiaeum 'Aucubaefolia' leaves has attracted high demand in the floriculture crop industry. The stimulatory effect of rooting hormone (indole-3-butyric acid; IBA) and rooting media on adventitious root growth of 'Aucubaefolia' was evaluated. The study was conducted as two experiments to determine the rooting performance of ‘Aucubaefolia’ stem cuttings. The first experiment was designed to test the rooting performances of unrooted cuttings after a 48-hour cold storage condition at 21°C. The influence of rooting media and IBA on the development of rooted cuttings was assessed in experiment two. Coir dust and jiffy pellet were tested as two media and 0 mg·L-1, 250 mg·L-1, 500 mg·L-1, and 1000 mg·L-1 were tested as four concentrations of IBA. The most significant effects were shown by rooting media on the rooting of ‘Aucubaefolia’ stem cuttings. Among the two media, the jiffy pellet reported the highest number of roots per cutting, root-to-shoot ratio, and average root diameter. The coir dust medium showed the minimum days to root initiation. The application of 500 mg·L-1 IBA experienced the highest number of roots in jiffy pellet medium. Subsequently, the vegetative propagation of C. variegatum ‘Aucubaefolia’ using stem cuttings was significantly influenced by the rooting medium and IBA concentration.